ظاهرة الرق فى مصر خلال عصري الدولة الوسطى و الحد يثة - قانة.وفاء (University of Eloued جامعة الوادي, 2024)
تهدف هذه الدراسة إلى إبراز ظاهرة الرق في مصر القديمة خلال عصري الدولة الوسطى و الحديثة ، و قد توصلت إلى أن مشكلة الرق والاسررقاق في مصر شهدت تطورا كبيرا في هذا الصدد خلال فررتي الدولة الوسطى والحديثة. حيث كانت ظاهرة الرق ظاهرة شائعة في تلك الفررة ولكن كانت ترغير طبقا للظروف الاجرماعية و الاقرصادية. ويمكن تقسيم المجرمع المصري في تلك الفررة إلى طبقرين رئيسيرين؛ النبلاء و الأرقاء. وكان النخبة الحاكمة تمرلك العديد من الرقيق الذين كانوا يعملون في الزراعة والبناء والخدمات الأخرى. بينما كان الاسررقاق يخرلف بين الرقيق الذين كانوا يعملون في حقول ملوك مصر والفنانين والحرفيين. وقد شهدت فررة الدولة الحديثة في مصر زيادة في اسرخدام الرقيق في العديد من الصناعات والزراعة، وكانوا يعربرون ملكية لأصحابهم وليس لديهم أي حقوق اجرماعية أو اقرصادية. ولقد كان للرق انعكاسات في مصر على الأوضاع العامة خلال عصري الدولة الوسطى و الحديثة في الجوانب السياسية و العسكرية و الاقرصادية والاجرماعية لمصر القديمة في عهد الدولة الوسطى و الحديثة. Summary of the research : This study aims to highlight the phenomenon of slavery in ancient Egypt during the Middle and New Kingdom eras, and it has concluded that the problem of slavery and slavery in ancient Egypt witnessed great development in this regard during the Middle and New Kingdom periods. Slavery was a common phenomenon in that period, but it changed according to social and economic conditions. Egyptian society in that period can be divided into two main classes: Nobles and slaves. The ruling elite owned many slaves who worked in agriculture, construction, and other services, While slavery differed between the slaves who worked in the fields of the kings of Egypt and the artists and craftsmen. The New Kingdom period in Egypt witnessed an increase in the use of slaves in many industries and agriculture. They were considered the property of their owners and had no social or economic rights. Slavery had repercussions in Egypt on the general conditions during the Middle and New Kingdom eras in the political, military, economic and social aspects of ancient Egypt during the Middle and New Kingdom era.
1077-2050 ق.م
Keywords: الرق; مصر القديمة; الفراعنة; ancient Egypt; slavery; Pharaohs